Scouting Culture and Its Relationship with Scouting Curricula According to the Sustainable Development Goals Perspective among Scout Leaders in Iraq - Magda Abbas Muhammad Ali; Mahmoud Dawood Al-Rubaie; Amna Fadel Mahmoud (Institute of Medico-legal Publications Pvt Ltd, 2021)
The development aims to achieve continuous progress in the life and well-being of all residents and is basedon the effective and professional contribution of all individuals to development, and the fair distribution ofits revenues, which requires a scouting leadership that can keep pace with the innovations in society andcan meet the requirements of society focused on preparing a positive citizen who contributes to a solutionHis problems and the problems of his society. The educational institutions in some countries have paidgreat attention to scouting because of its positive effects represented in achieving the advancement andadvancement of societies, in addition to a course in strengthening the sense of citizenship and belongingto members of society, as well as contributing to community participation and development, as Scoutingis one of the pillars of volunteer work. Educators have unanimously agreed on the importance of Scouteducation and its effective role in achieving its goals. Its goal is to build a good citizen by contributing to theeducation and development of youth to achieve the maximum advancement of their physical, mental, socialand spiritual capabilities as good individuals and responsible citizens and members in their local, nationaland global societies, and the research aims to build a scale The reality of the Scout curricula according tothe perspective of the Sustainable Development Goals of Scout leaders in Iraq, and identifying the level ofreality of the Scout curricula according to the perspective of the Sustainable Development Goals amongscout leaders in Iraq.